2018
DOI: 10.1371/journal.pone.0203645
|View full text |Cite
|
Sign up to set email alerts
|

Nepalese migrants in Japan: What is holding them back in getting access to healthcare?

Abstract: IntroductionMigrants are one of the most deprived and vulnerable groups who receive the least health services in the society. Only a few studies have been conducted on access to healthcare among migrants in Asia, despite hosting 75 million migrants. In Japan, Nepalese migrants constitute the largest South Asian community. Their number increased by three folds from 2011 to 2016. However, little is known about their access to health care in Japan. Based on Andersen's model, we examined the factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 34 publications
1
32
2
1
Order By: Relevance
“…Two studies enrolled non-pregnant migrants41 42 and eight exclusively analysed mothers 43–50. The remaining nine studies were of general migrant populations of a single (n=5) or various (n=4) nationalities 51–59. There were 10 studies specifically examining Brazilians of Japanese descent, making them the most studied nation-specific migrant subgrouping in terms of mental well-being 60–70…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies enrolled non-pregnant migrants41 42 and eight exclusively analysed mothers 43–50. The remaining nine studies were of general migrant populations of a single (n=5) or various (n=4) nationalities 51–59. There were 10 studies specifically examining Brazilians of Japanese descent, making them the most studied nation-specific migrant subgrouping in terms of mental well-being 60–70…”
Section: Resultsmentioning
confidence: 99%
“…The number of subjects per study ranged from 3 to 1,252, with a median size of 119. Importantly, a small number of migrants (<75) were explicitly not enrolled in a health insurance plan; the only studies that listed this variable were those of Nepalese51 or Brazilians migrants 60–70…”
Section: Resultsmentioning
confidence: 99%
“…The total possible scores ranged from zero to 21. This questionnaire has been previously used in another study of migrants in Japan [ 23 , 25 ]. The Cronbach's alpha coefficient was 0.84 for this study.…”
Section: Methodsmentioning
confidence: 99%
“…A higher incidence of tuberculosis has been reported among migrants than among the Japanese population due to delayed access to treatment [22]. A study among Nepalese migrants in Japan showed that around 32% of them did not visit the doctor or health worker when needed, which was mostly due to language and health insurance related barriers [23]. Such barriers may also limit migrants' utilization of HIV testing in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…As there are numerous insurance schemes in Japan, it is di cult to obtain exact gures regarding coverage among foreign residents. According to reports from some local governments and NGOs, however, it has been estimated that approximately 80% of foreign residents are covered by a Japanese public insurance scheme (7,8,22). This shows a dramatic improvement in coverage in recent decades, as in 2004 a survey conducted by a local government reported that this gure was 64.4% (27).…”
Section: Discussionmentioning
confidence: 99%